Representasi Cinta dalam Novel Kau, Aku, dan Sepucuk Angpau Merah Karya Tere Liye : Analisis Tematik Model Robert Sternberg - Syarifah Aeni Maulida; Sulastriningsih Djumingin; Aswati Asri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to describe the representation of love in the novel Kau, Aku, dan Sepucuk Angpau Merah by Tere Liye using Robert Sternberg's Love Triangle theory which includes three main components, namely intimacy, passion, and commitment. The research method used is descriptive qualitative with a thematic analysis approach. The research data are in the form of quotations in the novel that contain elements of love based on the three main components of Robert Sternberg's theory (1986). The analysis process is carried out through the stages of data reduction, classification, and interpretation of the meaning of the quotations in accordance with the theoretical framework used. The results of the study show that the novel Kau, Aku, dan Sepucuk Angpau Merah represents love in a deep and complex way through its three components: 1) intimacy is depicted through emotional closeness, sincere attention, and warmth of the relationship between the characters Borno and Mei; 2) passion is seen through feelings of longing, emotional attraction, and inner turmoil described with symbolic and reflective language; and 3) commitment is the most dominant aspect, shown through an attitude of loyalty, determination, and sincerity to love even if it means letting go. Furthermore, combined forms of love, such as romantic love (intimacy and passion) and friendly love (intimacy and commitment), enrich the dynamics of relationships between characters. This research confirms that Tere Liye's works present love stories not only as a form of romance, but also as a reflection of human emotional and moral maturity. Thus, this research contributes to the development of psychological literary studies and strengthens the relevance of Robert Sternberg's theory of love in the analysis of modern Indonesian literary works.